1987
DOI: 10.1002/bjs.1800740426
|View full text |Cite
|
Sign up to set email alerts
|

Plunging ranula: A report of three cases and review of the literature

Abstract: Three cases of plunging ranula are reported and the literature reviewed. Extravasation of saliva from the sublingual gland due to trauma or obstruction of its ducts appears to be the most likely cause of plunging ranula. Available data suggest that the submandibular gland is usually not involved, although at the time of surgery it may be extremely difficult to exclude a submandibular origin of the cyst in the neck. Communication between the oral and cervical components of the plunging ranula probably occur via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 26 publications
0
31
0
5
Order By: Relevance
“…It may appear as a submandibular mass without visible intraoral involvement, in which case the diagnosis is more difficult. 8 There have been several subsequent reports, 3,9,10 but it remains an infrequent occurrence. [3][4][5] There is said to be a slight female preponderance of about 1.3:1 (F:M).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It may appear as a submandibular mass without visible intraoral involvement, in which case the diagnosis is more difficult. 8 There have been several subsequent reports, 3,9,10 but it remains an infrequent occurrence. [3][4][5] There is said to be a slight female preponderance of about 1.3:1 (F:M).…”
mentioning
confidence: 99%
“…8 It is generally accepted that the source of the problem is most commonly the sublingual gland, and experimentally, both partial severance 11 and ligation 12 of the sublingual duct in cats lead to sialocele formation, whereas ligation of the submandibular duct does not. 8 It is generally accepted that the source of the problem is most commonly the sublingual gland, and experimentally, both partial severance 11 and ligation 12 of the sublingual duct in cats lead to sialocele formation, whereas ligation of the submandibular duct does not.…”
mentioning
confidence: 99%
“…Marsupialisation has gained popularity not least because of its relative simplicity, but also because it involves only limited dissection and therefore a reduced risk of damage to adjacent structures. Recurrence however is unpredictable leading some authors to advocate a modified technique incorporating packing the cyst cavity (2). Contemporary opinion suggests that because mucoceles are pseudocysts there is no imperative to remove the cyst lining.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Davison et al 1 suggested that removal of the SLG via either a cervical or an intraoral approach is important and that excision of the pseudocyst is probably unnecessary. Parekh et al 4 reviewed the literature and found the recurrence rate was 70% after incision and drainage of the cyst, 53% after marsupialization, 85% after excision of the cyst in the neck, and 2% after excision of the SLG via a cervical or an intraoral route. Therefore, they suggested that excision of the SLG with intraoral drainage of the cervical swelling is the treatment of choice for plunging ranula.…”
Section: Discussionmentioning
confidence: 99%
“…There is a general agreement to excise the ipsilateral SLG, but using a cervical approach remains controversial. 1,3–6 The cervical approach requires a cervical skin incision and is accompanied by the risk of impairment of the marginal mandibular branch of the facial nerve. We propose an intraoral method for surgical management of a plunging ranula utilizing an endoscope to confirm complete resection of the SLG.…”
Section: Introductionmentioning
confidence: 99%